Radiation‐Belt Dropouts: Relationship With Geomagnetic Storms and MeV Precipitation - Domenique Freund; Lauren Blum; Jinbei Huang; Sergio Vidal‐Luengo; Alessandro Bruno; Ryuho Kataoka (Geophysical Research Letters)
Abstract To better understand rapid radiation belt losses, this statistical study examines dropouts, defined as a phase‐space density (PSD) decrease by a factor of ≥5 within 8 hr. The relationship between dropouts, storm parameters, solar‐wind drivers, geomagnetic indices, and MeV electron precipitation is analyzed. Four years of data from the Van Allen Probes, measuring electron density, the CALorimetric Electron Telescope on the International Space Station, measuring MeV electron precipitation, and solar‐wind/magnetic indices from the OMNI dataset are utilized. Our investigation reveals that electron loss in PSD increases with disturbance intensity. However, about one‐third of dropouts occur during small geomagnetic disturbance periods, some involving precipitation, while approximately 40% of storms do not lead to dropouts. Superposed epoch analysis identifies solar‐wind density and dynamic pressure as the main dropout drivers, while precipitation becomes more likely with higher trapped electron flux and stronger substorms. Dropouts do not require a negative southward magnetic field component.